The Effect of Creative Arts Therapy on Stress Level and Blood Pressure of The Elderly With Hypertension - Utami, Putu Ayu Sani; Sulistiowati, Ni Made Dian; Karin, Putu Ayu Emmy Savitri (Journal of A Sustainable Global South; Vol 5 No 2 (2021): August 2021, 2021)
The elderly are vulnerable to hypertension due to the accumulation of unhealthy lifestyles for a long time and can be exacerbated by the stress due to the inability to adapt to the decline in physical conditions, changes in roles and social relations, economic ability, degenerative diseases and treatment in the long term. Risk factors for hypertension can caused by stress. Stress management can be done with a combination of creative arts therapy that is singing, drawing, and storytelling which has a relaxing effect. This study aims to determine the effect of creative arts therapy on stress levels and blood pressure of the elderly with hypertension in Kesiman Kertalangu Village, East Denpasar City, Bali, Indonesia. This research was a quasy experiment with pre-test and post-test design. Samples used were 63 elderly with hypertension who experience mild and moderate stress using simple random sampling technique divided into three groups of treatment with the amount 21 elderly of each groups. Stres level of of hypertension were evaluated using The Stress Assessment Questionnaire and blood pressure measurement using manometer. The main results of this study indicated that creative art therapy can reduce stress of the elderly significantly with p value 0.000<0.05. An average of blood pressure in creative art therapy has decreased. Wilcoxon test results showed the p value of  blood pressure (sistole;diastole) for singing (0.002;0.014), storytelling (0.009;0.008) and drawing (0.016;0.011) <0.05 which means that there is an effect of those therapy on elderly blood pressure. The results of the Ancova analysis showed no difference in blood pressure results after each intervention was given to the elderly (p value 0.244>0.05 for systole dan p value 0.738>0.05 for diastole). That means that each intervention has a similar effect on reducing blood pressure. Creative arts therapy provides a relaxing effect while performing art activities so that feeling calms down and stimulates the healing process. Further research with a larger population needs to be done to increase public awareness of the benefits of creative art therapy to reduce stress and blood pressure in the elderly with hypertension. Index Terms — : elderly, creative arts therapy, singing, drawing, story telling, hypertension